Exploration of High School Students' Problem-Solving Ability Based on Gender in Fluid Material - Fauzi, Toni Dwi; Handayanto, Supriyono Koes; Sunaryono, Sunaryono (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
This research explores high school students' problem-solving abilities based on gender in a static and dynamic fluid material. The type of research is quantitative descriptive research design. The population of this research was class XII students at one of the state schools in Malang, East Java. The sampling technique was purposive sampling, which was done by selecting students taught by the same teacher. The selected sample consisted of 115 students, 34 males and 81 females. The data in this study was collected by giving a test, where the test instrument used was seven essay questions on fluid material, which had a reliability coefficient of 0.70 (high). The data obtained was then analyzed using descriptive statistics, t-test, and the ANOVA test. The research results show differences in problem-solving ability between male and female students, where female students have higher problem-solving ability than male students in all problem-solving processes. The physics approach is the highest process mastered by students, while the mathematical procedure is the lowest. A physics problem-solving process is still in the low category, indicating that efforts are needed to improve students' problem-solving ability.